HBV Infection among HIV-infected cohort And HIV-negative Hospital attendees in South Western Nigeria (2014)
"Background: Prevalence, association and probable mode of acquisition of HBV and HIV dual infections have not been fully explored. Thus, HBV intervention plan and services are sometimes exclusively targeted towards HIV-infected population. We investigated HBV infection among HIV-infected cohort in comparison with HIV-negative hospital attendees to ascertain dual infectivity pattern; thereby encouraging appropriat allotment of intervention services. A total of 349 (M=141; F=208; Mean=33.98 years; Range= 0.33-80 years) plasma specimens from two virus diagnostic laboratories in south-western Nigeria were analysed. These include 182 HIV-positive and 167 HIV-negative specimens from ART and GDV laboratories respectively. The specimens were initially screened for detectable HIV antigen/antibody, and subsequently HBsAg by ELISA technique. Overall, HBsAg was detected in 20.92% (95% CI: 16.65-25.19%) of the patients. Also, 24.82% (95% CI: 17.69 31.95%) and 18.27% (95% CI: 13.02-23.52%) HBsAg positivity was recorded for males and females respectively. CHI square analysis showed no association (P=0.14) between gender and prevalence of HBsAg. Similarly, comparison of prevalence of HBsAg by age groups shows no significant difference (P=0.24). Overall, no significant difference (P=0.59) was observed in the prevalence of HBsAg among the HIV-infected cohort and HIV-negative hospital attendees. Results of the study confirm endemicity and comparable rates of HBV infection independent of HIV-status.